Uma proposta de WebQuest para a introdução ao letramento estatístico dos alunos da E.J.A. - Ribacionka, Márcia Cristina dos Santos (2010)
This research aims to verify whether the use of WebQuest teaching methodology allows the introduction of the statistical literacy of students in the Education of Young Adults and the 3rd year of high school, a public school in the state public network. The research methodology adopted was to design experiments, because it allows the teacher to work as a teacher and researcher and also to perform an experiment, reflect on teaching and learning by proposing its improvement. For this, we developed a didactic sequence using the proposed activities by Encceja in statistical literacy. In the verification of learning, students through the WebQuest, "Knowing the Region Where You Live", to use a spreadsheet, for the construction of graphical representations, the study of problems encountered in the region, a text editor to produce a document with proposed solutions and the socialization of knowledge held a seminar using a presentation editor. This study shows that it is possible to use a WebQuest to introduce the statistical literacy with the students of the EJA